2022
DOI: 10.3390/agronomy13010096
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Response of Greenhouse Gas Emissions from Precision Fertilization on Barley

Abstract: Precision fertilization is a promising mitigation strategy to reduce environmental impacts of N-fertilization, but the effective benefits of variable-rate fertilization have not yet been fully demonstrated. We evaluated the short-term response (23 days) of GHGs emissions following variable-rate fertilization on barley. Yields, biomass (grains + straw) and different N-use indicators (N uptake, grain protein concentration, recovery efficiency, physiological efficiency, partial factor productivity of applied nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In the structure of the share of GHG emissions in crop production, a significant source of this pollution is the use of mineral fertilisers (Fabbri et al, 2023). Emissions of GHG comes from N 2 O -due to its high greenhouse potential -from nitrogen fertiliser application.…”
Section: Resultsmentioning
confidence: 99%
“…In the structure of the share of GHG emissions in crop production, a significant source of this pollution is the use of mineral fertilisers (Fabbri et al, 2023). Emissions of GHG comes from N 2 O -due to its high greenhouse potential -from nitrogen fertiliser application.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have conducted relevant studies. Fabbri et al [47] found that precision fertilization can reduce nitrogen application by about 75%; Cillis et al [48] showed that conservation tillage can reduce CO 2 emission by about 56% compared with conventional tillage; Pretty and Bharucha [49] observed that comprehensive pest management projects can reduce pesticide use to 30.7%. The results of this study show that the best way for agricultural production trusteeships to reduce carbon emission is by reducing the use of fertilizers, and the second-best way is by reducing the use of agricultural chemicals.…”
Section: Effect Of Agricultural Production Trusteeship On Promoting C...mentioning
confidence: 99%
“…Other researchers conduct relevant studies. Fabbri et al ( 2022) [46] found that precision fertilization can reduce nitrogen application by about 75%; Cillis et al (2018) [47] showed that conservation tillage can reduce CO2 emission by about 56% compared with conventional tillage; Pretty and Bharucha (2015) [48] observed that comprehensive pest management projects can reduce pesticide use to 30.7%. The results of this study show that the best way for agricultural production trusteeship to reduce carbon emission is reducing the use of fertilizers, and the second best way is reducing the use of agricultural chemicals.…”
Section: Balance Testmentioning
confidence: 99%